2017
DOI: 10.1002/1873-3468.12709
|View full text |Cite
|
Sign up to set email alerts
|

Functional role of glycosphingolipids in contact inhibition of growth in a human mammary epithelial cell line

Abstract: We have demonstrated previously the involvement of certain glycosphingolipids (GSLs) in 'contact inhibition' (dependent on cell-to-cell contact) of cell growth. Here, we examined the roles of specific GSLs in contact inhibition of the human epithelial cell line MCF10A. Contact-inhibited cells show increased expression of the ganglioside GD3 and the globo-series GSL Gb3, and of the mRNAs for the corresponding sialyltransferases ST8SIA1 (GD3 synthase) and galactosyltransferase A4GALT (Gb3 synthase). siRNA knockd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…We further characterized the impacts of Gb3‐cSrc association on drug resistance in WiDr cells carrying the R273H TP53 mutation. Previous reports from other laboratories showed that addition of exogenous GM3, Gb3 and GD3 altered cell viability and other behaviors 50,51 . Shiga toxin 1B subunit (STxB or verotoxin) specifically bound to Gb3 and induced cancer cell death 52–54 .…”
Section: Resultsmentioning
confidence: 96%
“…We further characterized the impacts of Gb3‐cSrc association on drug resistance in WiDr cells carrying the R273H TP53 mutation. Previous reports from other laboratories showed that addition of exogenous GM3, Gb3 and GD3 altered cell viability and other behaviors 50,51 . Shiga toxin 1B subunit (STxB or verotoxin) specifically bound to Gb3 and induced cancer cell death 52–54 .…”
Section: Resultsmentioning
confidence: 96%
“…The enzyme encoded by the A4GALT gene catalyzes the synthesis of P1 and PK antigens and is also widely used in P1PK blood group systematic typing due to its gene polymorphism [34] . In addition, studies have reported that knocking down A4GALT can significantly inhibit contact inhibition, and exogenous adding A4GALT can inhibit the proliferation of low-density cells, suggesting that A4GALT is involved in the 'contact inhibition' of cell growth [35] . Other studies have found that A4GALT-mediated GSLs can enhance the metastasis ability of mesenchymal and epithelial cancer cells, and the loss of A4GALT mediated by CRISPR-Cas9 can weaken galactose induced epithelial-mesenchymal transformation (EMT) [36] .…”
Section: Discussionmentioning
confidence: 99%
“…Cholera toxin is produced by Vibrio cholerae and is a multifunctional protein that influences various cells, including the immune system, and which also acts as an anti-inflammatory agent (Beharati K and Ganguly NK, 2011; Baldauf K et al, 2015). Cholera toxin was shown to suppress carcinogenesis in colon cancer (Doulberis M et al, 2015) and may exert contact inhibition by binding to glycosphingolipids in MCF10A cells (Huang X et al, 2017). One of the functions of cholera toxin is to activate adenylate cyclase, which increases the intracellular cAMP level.…”
Section: Discussionmentioning
confidence: 99%